PENGARUH RESILIENSI, ETOS KERJA DAN SELF AWARENESS TERHADAP KINERJA KARYAWAN - Putri, Fauziah Fidaroini; Mujanah, Siti (STAI Darul Qalam Tangerang, 2023)
This study aims to analyze the Effect of Resilience, Work Ethic and Self Awareness on the Performance of employees. The type of research used is quantitative and this study uses 75 employees of some company in Surabaya. The data collection method used is the survey method with a questionnaire instrument. And the analysis data used in this research were multy regression analysis to analysis the effect of independent variables to dependen variable. And to test the hypothesis used t-test and f-test. The result of analysis showed that the Resilience, Work Ethic and Self Awareness significantly have influence as individual and simultaneously on Employee Performance. This research is expected to be a consideration to develop better employee performance. Its mean that this research is expected to be a consideration for the development of human resources in the company on manage their employees